Clinical significance of endothelial vasodilatory function evaluated by EndoPAT in patients with systemic sclerosis. Issue 6 (30th March 2020) - Aozasa, Naohiko; Hatano, Masaru; Saigusa, Ryosuke; Nakamura, Kouki; Takahashi, Takehiro; Toyama, Tetsuo; Sumida, Hayakazu; Tamaki, Zenshiro; Maki, Hisataka; Minatsuki, Shun; Komuro, Issei; Sato, Shinichi; et al.
Abstract: Endothelial dysfunction is a hallmark of vasculopathy associated with systemic sclerosis (SSc). Reactive hyperemia peripheral arterial tonometry is a rapid and non‐invasive technique to assess peripheral microvascular endothelial function by measuring changes in digital pulse volume during reactive hyperemia. Low scores of the reactive hyperemia index (RHI) imply an impaired vasodilatory response and, accordingly, impaired endothelial and vascular health. To investigate the clinical significance of the RHI in SSc patients, RHI values were measured in 43 SSc patients and 10 healthy controls. In diffuse cutaneous SSc (dcSSc) patients, RHI values were significantly decreased compared with healthy controls, and inversely correlated with disease duration. In total SSc patients, there was a significant inverse correlation between RHI values and skin score, and interstitial lung disease was associated with the decrease in RHI values. Among vascular symptoms, the current and past history of digital ulcers was seen more frequently in patients with decreased RHI values than in those with normal RHI values. Although no SSc patients had pulmonary arterial hypertension, an inverse correlation was evident between RHI values and mean pulmonary arterial pressure measured by right heart catheterization. These results indicate that the decrease in RHI values is associated with skin fibrosis, interstitial lung disease, digital ulcers and pulmonary vascular involvement leading to pulmonary arterial hypertension, supporting the canonical idea that endothelial dysfunction is a critical event underlying the development of tissue fibrosis and vascular complications in SSc.